Non-Muscle Myosin II Is Essential for the Negative Regulation of B-Cell Receptor Signaling and B-Cell Activation - Seeley-Fallen, Margaret K.; Lazzaro, Michelle; Liu, Chaohong; Li, Quan-Zhen; Upadhyaya, Arpita; Song, Wenxia (Frontiers in Immunology, 2022)
Antigen (Ag)-triggered B-cell receptor (BCR) signaling initiates antibody responses. However, prolonged or uncontrolled BCR signaling is associated with the development of self-reactive B-cells and autoimmune diseases. We previously showed that actin-mediated B-cell contraction on Ag-presenting surfaces negatively regulates BCR signaling. Non-muscle myosin II (NMII), an actin motor, is involved in B-cell development and antibody responses by mediating B-cell migration, cytokinesis, and Ag extraction from Ag-presenting cells. However, whether and how NMII regulates humoral responses through BCR signaling remains elusive. Utilizing a B-cell-specific, partial NMIIA knockout (cIIAKO) mouse model and NMII inhibitors, this study examined the role of NMII in BCR signaling. Upon BCR binding to antibody-coated planar lipid bilayers (PLB), NMIIA was recruited to the B-cell contact membrane and formed a ring-like structure upon B-cell contraction. NMII recruitment depended on phosphatidylinositol 5-phosphatase (SHIP1), an inhibitory signaling molecule. NMII inhibition by cIIAKO did not affect B-cell spreading on PLB but delayed B-cell contraction and altered BCR clustering. Surface BCR “cap” formation induced by soluble stimulation was enhanced in cIIAKO B-cells. Notably, NMII inhibition by cIIAKO and inhibitors up-regulated BCR signaling in response to both surface-associated and soluble stimulation, increasing phosphorylated tyrosine, pCD79a, pBLNK, and pErk and decreasing phosphorylated SHIP1. While cIIAKO did not affect B-cell development, the numbers of germinal center B-cells were significantly increased in unimmunized cIIAKO mice, compared to control mice. While cIIAKO mice mounted similar antibody responses when compared to control mice upon immunization, the percentages of high-affinity antibodies, Ag-specific germinal center B-cells, and isotype switched B-cells were significantly lower in cIIAKO mice than in control mice. Furthermore, autoantibody levels were elevated in cIIAKO mice, compared to control mice. Collectively, our results reveal that NMII exerts a B-cell-intrinsic inhibition on BCR signaling by regulating B-cell membrane contraction and surface BCR clustering, which curtails the activation of non-specific and self-reactive B-cells.